La figure de la mère de soldat dans le discours nationaliste israélien : de l’assignation nationale à la ressource militante (1948-2019) - Valérie Pouzol (Genre & Histoire)
In the context of the project (1937) and then the vote (1947) concerning the territorial partition of Palestine, the demographic challenges and uncertainty linked to the need to retain the territory led various currents of political Zionism to impose upon Jewish women a constantly renewed injunction to bear children and become mothers. This demand, far from locking them into the sole social role of “fertile bellies”, led some of them to use their status as mothers to oppose projects of territorial expansion and the automatic preference for military options. Mothers’ groups regularly intervened to propose an alternative to military conquest, to the separation process and to the violence of war. In Israel up until the present day, women’s as well as men’s voices have raised the question of consent to the sacrifice of their children.